The Development of a Laboratory Simulation to Study the Surface Temperature Effect On Corrosion Under Insulation Formation - Azizan, Muhammad Akmal; Ismail, Azzura; Md Salleh, Salihatun; Mat Noor, Fazimah; Che Ismail, Mokhtar (Journal of Advanced Mechanical Engineering Applications, 2023)
Corrosion under insulation (CUI) refers to external corrosion that appears between carbon steel piping or pressure vessels’ external surfaces underneath jacketed insulation. There are many factors affecting the CUI corrosion rate. The chance of CUI exhibits a higher value between 50ºC and 175ºC. Understanding the corrosion rate at critical temperatures is important in assessing insulation performance and preparing maintenance plans. It is challenging to predict the CUI rate in a real working pipeline. A laboratory simulation following ASTM G189-07 is a laboratory scale to study and provide an alternative method for determining CUI corrosion rate at a controllable working temperature. At 80ºC, the CUI corrosion rate is lower than the CUI rate at 75ºC. The result shows that the corrosion rate on the carbon steel pipeline is not perpendicular to temperature.